"Society-Ready" and "Fire-Ready" Forestry Education in the United States: Interdisciplinary Discussion in Forestry Course Textbooks. Issue 3 (22nd February 2021) - De'Arman, Kindra Jesse; York, Richard F
Abstract: Changing environmental and social forestry contexts present new challenges for forestry graduates. In contrast with previous generations, forestry students today must be prepared to handle the impacts of climate change and increasing fire severity and frequency, as well as critical human dimensions, including the need to collaborate with Native American nations. To explore the extent to which social and fire science is taught in forestry programs and how it has changed over time, we conducted a content analysis of prominent forestry course textbooks used in graduate programs in the United States. We found little change between texts published before and after 2000, except for an increase in discussion of climate change. Of the currently used textbooks, we found a significant variation in whether they included discussion of traditional ecological knowledge, prescribed burning, combined economic factors, logging, and whether they recommended prescribed burning and logging. Given that not all programs offer or require courses that specialize in these topics, many forestry students may be missing relevant interdisciplinary social-fire education that is necessary to handle contemporary and changing forestry issues.